1991
DOI: 10.2135/cropsci1991.0011183x003100040031x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Morphological Traits Conferring Bird Resistance to Sunflower across Different Environments

Abstract: Bird depredation is a major concern of sunflower (Helianthus annuus L.) producers wherever the crop is grown in the world. Development of bird‐resistant varieties would provide an economical, environmentally safe method of contending with the problem. Morphological traits that confer resistance to depredation by birds have been identified. These traits include long involucral bracts, horizontally oriented heads, concave heads, and long head‐to‐stem distances. The objective of this study was to determine the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Sağlam and Önemli (2005) reported in a similar study that plant characteristics of varieties were more important in the effect of bird damage on crops, especially those with sloping tablets, which were less affected. Likewise, some researchers have found that there are significant differences between varieties in terms of bird damage, and that especially oblique, concave and brachy leaves whose trays are parallel to the ground with ninety degrees angle make bird damage less (Gross et al, 1991;Çoşke and Ulukan 2005;Rauf et al, 2008). The results of research carried out earlier on the plant characteristics of varieties and the results of this research are similar.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Sağlam and Önemli (2005) reported in a similar study that plant characteristics of varieties were more important in the effect of bird damage on crops, especially those with sloping tablets, which were less affected. Likewise, some researchers have found that there are significant differences between varieties in terms of bird damage, and that especially oblique, concave and brachy leaves whose trays are parallel to the ground with ninety degrees angle make bird damage less (Gross et al, 1991;Çoşke and Ulukan 2005;Rauf et al, 2008). The results of research carried out earlier on the plant characteristics of varieties and the results of this research are similar.…”
Section: Resultssupporting
confidence: 76%
“…In the 1980s oil of high-quality and efficient hybrid varieties were initiated to be developed, which would reduce bird damage the most. In these studies, species with a thick fibrous body with concave tops, high antioxidant crust, long stem and long brache leaves, more than 15 cm between the stem distance and the table and looking downward as resistant to bird damage were obtained (Gross et al, 1991). In this study, it was aimed to determine the harmfulness of seed yield of birds and the effect of variety characteristics on bird damage by growing 10 different hybrid sunflower cultivars in Kavak district of Samsun province.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed their resistance to feeding by birds in the field and in the laboratory, and compared various seed, plant, and agricultural characteristics to those of a bird-susceptible control F1 hybrid cultivar, 63M80. Gross and Hanzel (1991) identified long involucral bracts, horizontally oriented heads, concave heads, and long head-to-stem distances as features that confer resistance to feeding by birds. In our study, head-to-stem distance was similar among the three cultivars so we could not assess this feature.…”
Section: Discussionmentioning
confidence: 99%
“…The goal was to develop a bird-resistant sunflower while maintaining palatability, yield, and oil content. Scientists surmised the features needed to inhibit perch-feeding and seed access included a flat or concave head shape, tightly held achenes, thick fibrous hulls, hulls with high levels of anthocyanins, long chaffs, long wrap around bracts, a head-to-stem distance of more than 15 cm, and ground-facing flowers (Parfitt 1984;Seiler and Rogers 1987;Gross and Hanzel 1991). Additionally, the percentage of oil, which is correlated with hull thickness, was thought to be a key reason for birds selecting particular varieties of sunflower (Mason et al 1991).…”
Section: Sunflowermentioning
confidence: 99%